The Effect of Tangible, Reliability, Responsiveness, Assurance and Empathy on Tourist Satisfaction in Dunia Fantasi Taman Impian Jaya Ancol After The Implementation of The Covid-19 Vaccination - Kahfi, Gustian Al; Nugraha, Rizki Nurul (Institut Pariwisata Trisakti, 2022)
This study aims to determine the tangible, reliability, responsiveness, assurance, and empathy for tourist satisfaction. The descriptive quantitative method uses a multiple linear regression analysis with the SPSS Program. The population in this study is the number of visitors in November and December 2021, with 545,312 people. The sample size used the Slovin formula with the results of 100 respondents. The sampling technique used is accidental sampling. The results showed that only the reliability variable partially had no significant effect on tourist satisfaction. Dunia Fantasi Taman Impian Jaya Ancol needs the implementation of strict health protocols, the availability of various interpretation boards, and regular maintenance of the cleanliness of tourist attractions to improve their performance in providing services to tourists. Continuous improvement in managing the execution of Dunia Fantasi Taman Impian Jaya Ancol will increase the positive image of tourist destinations, which is a long time will form tourist satisfaction. Keywords: Tangible, Reliability, Responsiveness, Assurance, Empathy, Tourist Satisfaction